2008
DOI: 10.1007/s10526-008-9164-y
|View full text |Cite
|
Sign up to set email alerts
|

Predation by Nesidiocoris tenuis on Bemisia tabaci and injury to tomato

Abstract: Tomato is the most important vegetable crop in Spain. The mirid bug Nesidiocoris tenuis (Reuter) commonly appears in large numbers in protected and open-air tomato crops where little or no broad-spectrum insecticides are used. Nesidiocoris tenuis is known to be a predator of whiteflies, thrips and several other pest species. However, it is also considered a pest because it can feed on tomato plants, causing necrotic rings on stems and flowers and punctures in fruits. Our objectives were to evaluate predation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
168
2
17

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(196 citation statements)
references
References 20 publications
9
168
2
17
Order By: Relevance
“…Our research group has reg-114 ularly observed over the last few years that the incidence of 115 whiteflies, in particular B. tabaci, was very low in both 116 protected and open-field tomato crops where N. tenuis was 117 successfully established. At first, we attributed this result to 118 active predation by N. tenuis, which typically lives in and 119 feeds on the upper growing parts of tomato plants, on 120 immature B. tabaci and, to a lesser extent, on B. tabaci 121 adults (Calvo et al 2009). However, we thought that pre-122 dation alone could not explain the extremely low densities of 123 B. tabaci adults landing on the apical parts of plants com-124 pared to conventional crops where pesticides were used.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our research group has reg-114 ularly observed over the last few years that the incidence of 115 whiteflies, in particular B. tabaci, was very low in both 116 protected and open-field tomato crops where N. tenuis was 117 successfully established. At first, we attributed this result to 118 active predation by N. tenuis, which typically lives in and 119 feeds on the upper growing parts of tomato plants, on 120 immature B. tabaci and, to a lesser extent, on B. tabaci 121 adults (Calvo et al 2009). However, we thought that pre-122 dation alone could not explain the extremely low densities of 123 B. tabaci adults landing on the apical parts of plants com-124 pared to conventional crops where pesticides were used.…”
mentioning
confidence: 99%
“…The hormones 254 ABA, indole-3-acetic acid (IAA), salicylic acid (SA), JA, 255 12-oxo-phytodienoic acid (OPDA) and JA-isoleucine (JA-256 Ile) were analyzed by ultra-performance liquid chroma-257 tography coupled to mass spectrometry (UPLC-MS) (Flors 258 et al 2008;Forcat et al 2008 291 ABA-and JA-induced responses 292 Because the ABA pathway is mainly activated in response 293 to abiotic stresses such as water stress or desiccation (Kahn 294 et al 1993;Maskin et al 2001;Ramirez et al 2009), and 295 this is a symptom that N. tenuis produces in tomato plants 296 (Calvo et al 2009), we decided to explore the effect of 297 ABA-induced responses on the preference of the herbivore 298 B. tabaci. For this purpose, the ABA-deficient tomato 299 mutant Sitiens and its near-isogenic wild-type (wt) parental 300 line were assessed (Asselbergh et al 2007;Rodriguez et al 301 2010) in the laboratory using an olfactometer.…”
mentioning
confidence: 99%
“…Among the key pests of tomato plants in this region are the tobacco whitefly Bemisia tabaci (Gennadius) (Homoptera: Aleyrodidae), which is the vector of the Tomato Yellow Leaf Curl Virus (one of the most damaging virus diseases of tomato) (Gabarra et al, 2006;Calvo et al, 2008), and the tomato borer Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae), which was recently introduced in the country (Urbaneja et al, 2009). Moreover, other pests such as leafminers of the genus Liriomyza, the thrips Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae), spidermites and other Lepidoptera can threaten the agricultural production of fresh market tomatoes (RobledoCamacho et al, 2009 (Chow and Heinz, 2005), is also released in the tomato crop at the beginning of the growing season (Van der Blom, 2002;Robledo-Camacho et al, 2009).…”
mentioning
confidence: 99%
“…Sánchez (2008), observó a nivel de campo que N. tenuis presentaba una dinámica poblacional típica de un depredador en el cultivo de tomate, porque su número se incrementaba y se reducía correlativamente a las densidades de la presa. Estos resultados sugieren que este mírido explota los recursos de la planta solo cuando las presas son escasas, pudiendo en este caso comportarse como plaga y producir daños en el cultivo (Calvo et al 2009). …”
Section: Hábitos De Alimentaciónunclassified
“…Aunque N. tenuis se conoce como una especie endémica de la Cuenca Mediterránea (Figura 5), también se ha citado en el norte de África, Japón, Australia, Islas del Pacífico, Norteamérica, Cuba, Venezuela (Kerzhner y Josifov 1999, Zappala et al 2013, Colombia (Valderrama et al 2007) e Irán (Linnavuori 2007 (Westwood) (Hemiptera: Aleyrodidae)] y de la polilla del tomate Tuta absoluta Meyrick (Lepidoptera: Gelechiidae), aunque su contribución en la regulación de plagas secundarias como trips, pulgones y ácaros es reconocida (Sánchez y Lacasa 2008, Calvo et al 2009). …”
Section: Distribuciónunclassified